2020
DOI: 10.1021/acs.macromol.9b01773
|View full text |Cite
|
Sign up to set email alerts
|

Internal Structure of Methylcellulose Fibrils

Abstract: Methylcellulose (MC) is a water-soluble cellulose derivative with a wide range of commercial applications. Upon heating, MC solutions reversibly form ∼15–20 nm diameter fibrils, which percolate into a fibrillar network, resulting in macroscopic gelation. Using mid-angle X-ray scattering (MAXS) and wide-angle X-ray scattering (WAXS), we have analyzed MC chain organization within fibrils aligned in dried films that have been stretched by over 300%. MAXS and WAXS show distinct anisotropic scattering features, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 43 publications
6
54
0
Order By: Relevance
“…The relation between the length of the polymer chains and the fibril suggests that the macromolecules are aligned parallel to the fibril axis. Another study by Schmidt et al 30 has confirmed that the subfibril structure is semicrystalline in nature. The crystalline structure that has been proposed is a two-chain monoclinic unit cell, with dimensions consistent with other cellulosic crystalline structures.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The relation between the length of the polymer chains and the fibril suggests that the macromolecules are aligned parallel to the fibril axis. Another study by Schmidt et al 30 has confirmed that the subfibril structure is semicrystalline in nature. The crystalline structure that has been proposed is a two-chain monoclinic unit cell, with dimensions consistent with other cellulosic crystalline structures.…”
Section: ■ Introductionmentioning
confidence: 87%
“…Additionally, fibril formation may be induced by the addition of salt [ 64 , 65 ]. Rather recently, the tightly packed core region of the fibers has been suggested to comprise semicrystalline twisted MC chain domains aligned along the fibril long axis and surrounded by amorphous and less-ordered regions [ 66 ]. The percolation of the semi-stiff fibril network contributes to the increased macroscopic gel stiffness and turbidity at elevated temperatures.…”
Section: Methylcellulose and Cellulose Nanocrystalsmentioning
confidence: 99%
“…A fibrillar gel network structure has been reported for MC polymers of molecular weights 150 kg mol À1 and higher, 36,56 but currently the precise microstructure of the material used in our study here (M w approximately 50 kg mol À1 , details given below) is still unknown. The material used in this study becomes optically turbid (Fig.…”
Section: Introductionmentioning
confidence: 88%